2017
DOI: 10.1016/j.kint.2016.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Circulating fibronectin contributes to mesangial expansion in a murine model of type 1 diabetes

Abstract: Fibronectin is ubiquitously expressed in the extracellular matrix, and its accumulation in the glomerular mesangium in diabetic nephropathy is associated with deterioration of renal function in these patients. However, the exact role of fibronectin in the pathogenesis of diabetic nephropathy remains unknown. To clarify this, we administered fluorescent-labeled plasma fibronectin to wild-type mice and found it to accumulate in the mesangium. Using liver-specific conditional-knockout mice to decrease circulating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 60 publications
1
18
0
1
Order By: Relevance
“…The immunohistochemistry analysis demonstrated that diabetes was associated with an increase in the intensity of immunostaining for collagen IV, fibronectin, and TGF-β 1 (Fig. 3a, b), which are the major ECM proteins that lead to the development of the mesangial matrix expansion in the status of DN [25]. Consistent with the immunohistochemical findings, the levels of mRNA encoding for fibronectin and TGF-β 1 were significantly greater in the D than in the ND group (Fig.…”
Section: Effect Of Aunps On the Renal Expression Of Fibrosis Angiogesupporting
confidence: 74%
“…The immunohistochemistry analysis demonstrated that diabetes was associated with an increase in the intensity of immunostaining for collagen IV, fibronectin, and TGF-β 1 (Fig. 3a, b), which are the major ECM proteins that lead to the development of the mesangial matrix expansion in the status of DN [25]. Consistent with the immunohistochemical findings, the levels of mRNA encoding for fibronectin and TGF-β 1 were significantly greater in the D than in the ND group (Fig.…”
Section: Effect Of Aunps On the Renal Expression Of Fibrosis Angiogesupporting
confidence: 74%
“…Hyperhomocysteinemia (HHcy), an increased plasma homocysteine (Hcy) level is prevalent among patients with chronic kidney diseases (CKD) [1]. The mesangial cell provides architectural support for glomerular capillary loops and are crucial players in the initiation and progression of many kidney diseases [2,3]. Increased glomerular mesangial cell apoptosis / proliferation and excessive accumulation of extracellular matrix (ECM) protein leads to glomerulosclerosis in CKD patients [4,5]; similar results are also reported in experimental CKD animals [6][7][8].…”
Section: Introductionmentioning
confidence: 71%
“…The imbalance between the synthesis and breakdown of the ECM induces glomerulosclerosis and tubulointerstitial fibrosis. Liver-specific FN conditional knockout mice had no circulating FN and these mice were protected from STD-induced T1D, renal fibrosis and albuminuria, suggesting a critical role of circulating FN in these events 6. The improvement of renal fibrosis in a hyperglycemic state is the most concerned aspect of the current treatment.…”
Section: Introductionmentioning
confidence: 99%